Pelatihan Digital Marketing untuk Generasi Z: Mengembangkan Produk Edukasi berbasis Online - Radeswandri; Vebrianto, Rian; Berlian, Mery; Thahir, Musa (Tasnim Journal for Community Service, 2025)
This community service program aimed to enhance digital marketing skills and develop online educational products among Generation Z. The program involved 32 participants with diverse backgrounds, predominantly aged over 24 years (59.4%) with high school/vocational education backgrounds (71.9%). Using a blended learning approach combining webinars, interactive online classes, and group mentoring, the program focused on fundamental digital marketing, social media marketing, and content creation. Evaluation results demonstrated significant success: 96.9% of participants showed improved digital marketing capabilities, with 87.5% implementing or currently implementing their acquired knowledge. The program achieved a 93.8% satisfaction rate, with participants reporting increased confidence (87.5%) and better understanding of reaching Gen Z audiences (84.4%). Key outcomes included the establishment of a content creator community, development of 6 online courses, and 7 participants actively working as educational content creators. The program successfully addressed the need for practical digital skills among youth while fostering digital entrepreneurship initiatives. Recommendations include implementing differentiated learning paths, establishing post-training mentoring programs, and strengthening industry collaborations for sustainable impact.